Butorphanol: Effects of a Prototypical Agonist-Antagonist Analgesic on κ-Opioid Receptors - Stephen Commiskey; Lir-Wan Fan; Ing K. Ho; Rob W. Rockhold (Elsevier, 2005)
The opioid analgesic, butorphanol (17-cyclobutylmethyl-3,14-dihydroxymorphinan) tartrate is a prototypical agonist-antagonist opioid analgesic agent whose potential for abuse has been the cause of litigation in the United States. With a published affinity for opioid receptors in vitro of 1:4:25 (µ:δ:κ), the relative contribution of actions at each of these receptors to the in vivo actions of the drug are an issue of active investigation. A body of evidence has been developed which indicates that a substantial selective action of butorphanol on the κ-opioid receptor mediates the development of tolerance to butorphanol and cross-tolerance to other opioid agonists; to the production of dependence upon butorphanol, particularly in the rodent; and to compensatory alterations in brain opioid receptor-effector systems. This perspective will identify the current state of understanding of the effects produced by butorphanol on brain opioid receptors, particularly on the κ-opioid receptor subtype, and on the expression of phosphotyrosyl proteins following chronic treatment with butorphanol. Keywords:: butorphanol, κ-opioid receptor, dependence, proteomics